2023
DOI: 10.3390/vaccines11091494
|View full text |Cite
|
Sign up to set email alerts
|

Natural Antibodies Produced in Vaccinated Patients and COVID-19 Convalescents Recognize and Hydrolyze Oligopeptides Corresponding to the S-Protein of SARS-CoV-2

Anna M. Timofeeva,
Sergey E. Sedykh,
Tatyana A. Sedykh
et al.

Abstract: The S-protein is the major antigen of the SARS-CoV-2 virus, against which protective antibodies are generated. The S-protein gene was used in adenoviral vectors and mRNA vaccines against COVID-19. While the primary function of antibodies is to bind to antigens, catalytic antibodies can hydrolyze various substrates, including nucleic acids, proteins, oligopeptides, polysaccharides, and some other molecules. In this study, antibody fractions with affinity for RBD and S-protein (RBD-IgG and S-IgG) were isolated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The groups of 25 donors each involved in this study were described in our previous work [ 14 ]. These are COVID-19 survivors who were then vaccinated with Sputnik V (Con + Vac group), COVID-19 survivors (Con group), and healthy peoples vaccinated with Sputnik V (Vac group).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The groups of 25 donors each involved in this study were described in our previous work [ 14 ]. These are COVID-19 survivors who were then vaccinated with Sputnik V (Con + Vac group), COVID-19 survivors (Con group), and healthy peoples vaccinated with Sputnik V (Vac group).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that S-IgG antibodies hydrolyze oligopeptides corresponding to the epitopes of the S-protein. Antibodies without affinity for the S-protein were not active in the hydrolysis of any oligopeptides that were used in this research [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been shown that the IgG of SLE patients is most active in the presence of Ca 2+ , Mg 2+ , Co 2+ , and Ni 2+ ions [16]. The increase in the activity of RBD-IgG and S-IgG during the hydrolysis of S-protein oligopeptides has been reported to occur in the presence of Ca 2+ ions [27].…”
Section: Effect Of Divalent Metal Ions On the Catalytic Activity Of I...mentioning
confidence: 99%